Leadership style of the village head in driving the physical development of the village (study in Sungai Bawang Village Singingi District Kuantan Singingi Regency) - Fia Dwiristianti Yudiyanto (Central Research Institute for Agriculture (CeRIA), 2023)
This study aims to determine the Village Head's Leadership Style in Mobilizing Village Physical Development (Study in Sungai Bawang Village, Singingi District, Kuantan Singingi Regency). The Village Head is the head of a government organization that has a strategic position and has broad responsibilities. Village Development is a process of development activities that take place in the Village which covers all aspects of community life and livelihood. Leadership Style is an important role to achieve the success of one's leadership in an organization. The Village Head is the head of a government organization that has a strategic position and has broad responsibilities. Responsibilities in the village are matters of service tasks that are centered on the village head. The achievement of village development, the village government makes a development plan, the Village Medium Term Development Plan (RPJMDesa) is regulated in the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 114 of 2014 concerning Village Development Guidelines. Research Results The Head of Sungai Bawang Village is more dominant in using a participatory leadership style, although not fully used. The types and sources of research data are Primary Data and Secondary Data. Data collection techniques were Observation, Interview and Documentation techniques and this research was conducted in Sungai Bawang Village, Singingi District, Kuantan Singingi Regency with various selection of respondents taken from age, occupation, gender requirements.